Caracterização de três seringais manejados em terra firme, várzea e terra preta de índio no médio Amazonas - Araújo, Etelvino Rocha (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Seeking technical information to subsidize strategies to develop heveaculture in the Amazon state, a team of researchers of the National Institute of Amazon Research started in 2008 a descriptive research in rubber plantations in the Middle Amazon region, located in floodplain, in terra firme (TF) and indian black earth (TPI). In these areas we did: phytosociological characterization of the productive system; determination of the bark width; description of the tapping systems; characterization of the chemical fertility and soil granulometry; continued assessments of the river floods at the dry earth and floodplain areas; determination of pH; dry rubber content (DRC%), sucrose and inorganic phosphorus of latex; and quantification of the rubber production throughout the productive year. This research showed that the rubber trees studied are located in high plant density managed environments, characterized by the presence of water courses and integrated farming activities in the same area. These rubber trees are divided by the tappers in five different distinctions: purple bark, white bark, thick bark, yellow bark and barriguda . No soil physical restriction to the rubber tree‟s development was detected in the three areas, although the possibility of high phosphorus content associated to the low potassium content in the indian black earth soil, and the high base saturation in the floodplain soil appearing to be limiting factors for the rubber production in these areas needs further investigations. The river floods at the floodplain and terra firme areas in 2009 was longer and had higher water levels than in the years before, causing a reduction both in richness and diversity of species. We observed a great variation in productivity between the trees, and the mean values 7,59 and 11,97g/tree/tapping at the terra firme and floodplain areas might be below the potential of these areas, as the trees were not sufficiently stimulated by the tapping rhythm during 2009. Therefore rubber trees showed signs of under-exploitation: high values of pH, dry rubber content and sucrose, and low concentration of inorganic phosphorus, which shows a low metabolic activity of the laticiferous vessels during the exploitations.